Sustainable Entrepreneurship Education: A Systematic Bibliometric Literature Review - Rosário, Albérico Travassos; Raimundo, Ricardo (Sustainability, 2024)
The importance of shifting to a sustainable economy, based on new capabilities that would enable us to cope with the current turbulent changes is paramount. Entrepreneurs with sustainable concerns are considered to play a key role in the process by creating innovative, proactive, and risk assumption solutions, with both environmental and economic value. To date, there is no consensus on what capabilities education should provide so to create sustainable entrepreneurs able to cope with sustainability challenges. This piece of literature aimed to identify relevant factors for sustainable entrepreneurship education. Bibliographic databases were searched for documents published between 2012 and June 2023 to categorize central issues discussed in the literature on sustainable entrepreneurship education. The review process identified 61 empirical and non-empirical papers on sustainable entrepreneurship education (SEE). Data analysis revealed diverse models for sustainable entrepreneurship education (SEE) developed for use in both higher education institutions and secondary schools. Future research directions are underscored.